1989
DOI: 10.1136/ard.48.4.336
|View full text |Cite
|
Sign up to set email alerts
|

Atypical mycobacterial infection of the lung in rheumatoid arthritis.

Abstract: LiverpoolSUMMARY Mycobacterium kansasii was isolated from a cavitating pneumonia found in a 51 year old man with seropositive rheumatoid arthritis, and treatment was complicated by drug induced neuropathy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1994
1994
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…RA is one of the risk factors in atypical Mycobacterium infections; this may be a result of disease-related, impaired cell-mediated immunity and antibody-producing capacity, or the reduced chemotactic responses of polymorphonuclear cells. 4 It has also been reported that CD4ϩ T cells and γ/d T cells from MAC patients were defective in inducing anti-MAC activity. 8 T-cell-dependent growth inhibition and production of interferon-γ and macrophage colony-stimulating factor decreased in those patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…RA is one of the risk factors in atypical Mycobacterium infections; this may be a result of disease-related, impaired cell-mediated immunity and antibody-producing capacity, or the reduced chemotactic responses of polymorphonuclear cells. 4 It has also been reported that CD4ϩ T cells and γ/d T cells from MAC patients were defective in inducing anti-MAC activity. 8 T-cell-dependent growth inhibition and production of interferon-γ and macrophage colony-stimulating factor decreased in those patients.…”
Section: Discussionmentioning
confidence: 99%
“…[3][4][5][6][7] Almost all patients received corticosteroids with or without immunosuppressive drugs. We report here two cases of RA with atypical mycobacteriosis, even though no immunosuppressive agents were used.…”
Section: Introductionmentioning
confidence: 99%
“…They suggested that RA would be associated with NTM pulmonary diseases even in the absence of treatment with immunosuppressant agents. Watkin et al reported a case of Mycobacterium kansasii pulmonary disease with RA and discussed whether the suppression of cellular immunity or immunosuppression mediated by neutrophils would increase the tendency of infection in RA patients (12). In recent times, more aggressive treatment of RA with biological drugs is recommended.…”
Section: F I G U R E 4 Gr a N U L O Ma I N T H E C A V I T Y Wa L Lmentioning
confidence: 99%